Quranic views on industrialization sector - Zainan Nazri, M.K.N.; Ahmad, M.; Zainan Nazri, N.J.; Mat Ishak, M. (2012)
This study looks at the Quranic teaching, which are the Quran is not against industrialization. It is undeniable that Islam is a perfect way of life, it encourages industrialization and sets its pristine teachings as enshrined in the Qur’an and Sunnah of the Prophet (p.b.u.h) as the guiding principles and values for Muslims to create a kind of industrialization that shall bring about not only economic prosperity and sustainable development to the nation, but also one that is in harmony with the environment. The main objectives of this research are to deliberately aim at focusing an Islamic point of view (Quran) about the industrialization from both Western and Islamic perspectives. Its main emphasis is to identify which ones of the ideological underpinnings, which have been the driving philosophy behind the process of industrialization implemented in Malaysia, that are running counter with the universal values and teachings of Islam. The research bases on the Quranic concept of industrialization and prophetic traditions that related with the principles and values for Muslims to create a kind of industrialization. This research is conducted through the study consists primarily of historical research in nature and purely relies on library research in order to achieve the objectives of this research. A textual and critical analysis of Quranic verses will be utilized to demonstrate the application of Quran pertaining to industrialization. Apart from that in this study, the researcher will attempt to present the concept of industrialization from the Quranic point of view with special reference to selected Qur’anic verses which are found.This study will concentrate on examining industrialization in Malaysia from the Qur’anic perspective. He will use approximately five Quranic verses related to industrialization. In order to grasp and benefit from the virtues of the Prophet traditions, this research mentioning the various types of industrialization. The ideas presented could be further developed and appreciated by the Islamic society in related discipline.